2002
DOI: 10.1046/j.1365-3180.2002.00294.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered acetyl‐coenzyme A carboxylase confers resistance to clethodim, fluazifop and sethoxydim in Setaria faberi and Digitaria sanguinalis

Abstract: Populations of Setaria faberi and Digitaria sanguinalis cross-resistant to sethoxydim and fluazifop-P-butyl were identified in a vegetable cropping system in Wisconsin, USA, in 1991 and 1992 respectively. Experiments were conducted with partially purified acetyl-CoA carboxylase (ACCase) to determine whether resistance to sethoxydim and other ACCase inhibitors in S. faberi and D. sanguinalis resulted from altered enzyme activity. Based on I 50 values (the herbicide dose that inhibited ACCase activity by 50% com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 36 publications
4
32
0
3
Order By: Relevance
“…In most weeds showing resistance to inhibitors of the enzyme ACCase, this is attributed to alterations in the site of action of the enzyme (Volenberg & Stoltenberg, 2002). However, there are reports correlating resistance to ACCase inhibitors with metabolic processes (Bravin et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In most weeds showing resistance to inhibitors of the enzyme ACCase, this is attributed to alterations in the site of action of the enzyme (Volenberg & Stoltenberg, 2002). However, there are reports correlating resistance to ACCase inhibitors with metabolic processes (Bravin et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Embora existam vários mecanismos de resistência associados aos herbicidas inibidores da ACCase, a maioria dos casos estudados demonstra que a resistência é conseqüência da insensibilidade enzimática (De Prado et al, 2004;Volemberg & Stoltenberg, 2002). Aparentemente, os diferentes níveis de resistência cruzada apresentados pelos biótipos podem ser explicados pela existência de diferentes padrões da mutação enzimática (Volemberg & Stoltenberg, 2002;Carvalho, 2004) e, também, pelas características de eficácia intrínsecas a cada molécula.…”
Section: Resultsunclassified
“…Aparentemente, os diferentes níveis de resistência cruzada apresentados pelos biótipos podem ser explicados pela existência de diferentes padrões da mutação enzimática (Volemberg & Stoltenberg, 2002;Carvalho, 2004) e, também, pelas características de eficácia intrínsecas a cada molécula. Ainda, supõe-se que a mutação selecionada em determinada região esteja diretamente relacionada com os produtos mais aplicados na área.…”
Section: Resultsunclassified
“…When the same population was sprayed with imazethapyr, nicosulfuron or clethodim few to no plants survived (Stoltenberg and Wiederholt 1995). In a similar study, S. faberi cross resistance to fluazifop-P-butyl was identified in a vegetable cropping system in Wisconsin where the resistant biotype was 10.6-and 319-fold more resistant than the susceptible biotype (Volenberg and Stoltenberg 2002a). Greenhouse experiments have shown that the outcrossing rates between ACCase susceptible and ACCase resistant parent plants are low and range from 0.24 to 0.73% (Volenberg and Stoltenberg 2002b).…”
Section: Herbicide Resistancementioning
confidence: 94%